(untitled) (Journal for Freedom of Conscience (Jurnalul Libertății de Conștiință), 2017)
Problematic public articulation between religion and politics focused around the elusive meaning of the perfect freedom, desired or experienced, is a reality that is imposed on the human mind and which work the collective consciousness to format and legitimize a symbolic always seeking recognition. The analysis of the production of meaning proposed in this paper shows that the dominant expression of religious freedom which marks the thought of the actors in the public sphere is of the order of utopia, that the representation of religious freedom assumed by this perspective in the debates and social practices has a mythical nature and that meaning of religious freedom in the collective action is part of asilent idolatry in favor of a controversial democratic functioning.